2011
DOI: 10.1523/jneurosci.2817-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony Makes Neurons Fire in Sequence, and Stimulus Properties Determine Who Is Ahead

Abstract: The synchronized activity of cortical neurons often features spike delays of several milliseconds. Usually, these delays are considered too small to play a role in cortical computations. Here, we use simultaneous recordings of spiking activity from up to 12 neurons to show that, in the cat visual cortex, the pairwise delays between neurons form a preferred order of spiking, called firing sequence. This sequence spans up to ϳ15 ms and is referenced not to external events but to the internal cortical activity (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 102 publications
5
91
0
1
Order By: Relevance
“…It has been shown that internal sequences are locked to individual cycles of rhythmic excitatory waves (oscillations) in other brain structures (Ji and Wilson, 2007; Luczak et al, 2009; Peyrache et al, 2009; Havenith et al, 2011; Harvey et al, 2012; Xu et al, 2012; Carrillo-Reid et al, 2015; Markowitz et al, 2015; Mello et al, 2015). Thus, the same mechanism for sequence generation might be utilized not only in the hippocampus but also in other brain regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that internal sequences are locked to individual cycles of rhythmic excitatory waves (oscillations) in other brain structures (Ji and Wilson, 2007; Luczak et al, 2009; Peyrache et al, 2009; Havenith et al, 2011; Harvey et al, 2012; Xu et al, 2012; Carrillo-Reid et al, 2015; Markowitz et al, 2015; Mello et al, 2015). Thus, the same mechanism for sequence generation might be utilized not only in the hippocampus but also in other brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences generated in the absence of sensory cues have been observed in various cortical areas, basal ganglia, and the hippocampus (Wilson and McNaughton, 1994; Nádasdy et al, 1999; Louie and Wilson, 2001; Dragoi and Buzsáki, 2006; O’Neil et al, 2006; Foster and Wilson, 2006; Ji and Wilson, 2007; Lee and Wilson, 2002; Pastalkova et al, 2008; Luczak et al, 2009; Peyrache et al, 2009; Havenith et al, 2011; Harvey et al, 2012; Xu et al, 2012; Carrillo-Reid et al, 2015; Markowitz et al, 2015; Mello et al, 2015). These internally generated sequences seem to support mental functions such as cognitive planning, motor planning, visual memory, and episodic memory.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent neural networks (RNNs) consist of a reservoir of nodes or artificial neurons connected in some recurrent network structure (Maass et al, 2002;Jaeger and Haas, 2004). Typically, this structure is constructed at random, with only the output neurons connections trained to perform a given task.…”
Section: Active Information Storage In a Robotic Systemmentioning
confidence: 99%
“…For example, the LN model does not capture the effects of contrast adaptation, which includes a reduced gain (i.e., filter amplitude) at high contrast (Kim and Rieke, 2001; Meister and Berry, 1999; Shapley and Victor, 1978). The LN model also does not predict firing at high temporal resolution (Berry and Meister, 1998; Butts et al, 2016, 2007; Keat et al, 2001; Passaglia and Troy, 2004; Uzzell and Chichilnisky, 2004), and yet precise firing likely represents an essential element of downstream visual processing (Bruno and Sakmann, 2006; Havenith et al, 2011; Kelly et al, 2014; Wang et al, 2010a). …”
Section: Introductionmentioning
confidence: 97%